PENGARUH PERUBAHAN IKLIM DAN ANTISIPASI PENANGGULANGAN BENCANA KEBAKARAN LAHAN SERTA PENANAMAN POHON DI KUALA DUA - Sigit Sugiardi; Dina Octaviani; Arweni; Amung Hidayat; Sigit Nugroho Wahyu Jatmiko (LPPM ITB AAS Indonesia Surakarta, 2025)
Climate change in agricultural areas can affect the productivity of food crops. One of the impacts of climate change on the agriculture and forestry sectors is land fires caused by hot weather and lower rainfall. Forest and land fires increase the risk due to rising temperatures and drought caused by climate change. The Rasau area is an area with extensive peatlands and is currently widely used by the community as agricultural land. Excessive drainage dries out peatlands and makes them highly susceptible to fires. The potential for climate change is often exploited by the community to clear land by burning. PT. Kalbar Minerals Center Kalimantan Barat is the location where activities such as presentations, simulations, discussions, and tree planting take place, in collaboration with UPT KPH Kubu Raya. This community service initiative aims to provide the community with understanding and knowledge about climate change and encourage them to take proactive measures to mitigate land fire disasters. This activity aligns with the Key Performance Indicators (KPIs) of higher education institutions, which emphasize the importance of community service and addressing real-world issues within the community.